2022
DOI: 10.24036/sainstek/vol1-iss02/7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Study of Nigella sativa Bioactive Compound as E6 Inhibitor Against Human Papillomavirus (HPV) Infection

Ahmad Affan Ali Murtadlo,
Priscilla Listiyani,
Santika Lusia Utami
et al.

Abstract: HPV can trigger cancer cases in the laryngeal, lung, oral, and anogenital. Classification of HPV based on the ability to trigger cancer, HPV is divided into two types consisting of high risk (HR) and low risk (LR). HPV-6 and HPV-11 are low-risk types or only cause precancerous lesions or warts. In the case of lesion progression to intraepithelial malignancies triggered by infection with HPV-16 and HPV-18 types. Previous studies used E6 to target antiviral drug design, the drug works by inhibiting E6 activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Next, the molecular structure of Emodin is imported into the Pyrex software (https://pyrx.sourceforge.io/) for geometry optimization, which involves adjusting the Emodin molecule structure to obtain the most stable conformation. [15][16][17] The next step is docking analysis using the Pymol software to predict the molecular interactions between Emodin and Protein Kinase PIM1. In the docking analysis, Emodin is placed at the active site of Protein Kinase PIM1 to evaluate the affinity and potential interactions between the two.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the molecular structure of Emodin is imported into the Pyrex software (https://pyrx.sourceforge.io/) for geometry optimization, which involves adjusting the Emodin molecule structure to obtain the most stable conformation. [15][16][17] The next step is docking analysis using the Pymol software to predict the molecular interactions between Emodin and Protein Kinase PIM1. In the docking analysis, Emodin is placed at the active site of Protein Kinase PIM1 to evaluate the affinity and potential interactions between the two.…”
Section: Methodsmentioning
confidence: 99%
“…A deeper understanding of the potential of Thaflavine as a therapeutic agent in B-cell lymphoma can pave the way for the development of new therapies that are more effective and target-specific, improving treatment outcomes and patient prognosis. 5,6 To date, research on the use of natural compounds in the treatment of B-cell lymphoma is still evolving. Several previous studies have demonstrated the potential of natural compounds, including Thaflavine found in green tea (Camellia sinensis), as inhibitors targeting the BCl2 apoptosis regulator.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Lipinski Rule of Five (https://www.sciencedirect.com/topics/biochemistry-genetics-andmolecular-biology/lipinskis-rule-of-five) was employed to evaluate the physicochemical properties of Guaiacol and ensure that the compound meets the qualifying criteria as a potential drug. [19][20][21][22] The entire research process was conducted virtually through an in-silico approach, avoiding the need for expensive and time-consuming in-vivo experiments. This method provides an efficient and effective approach to analyzing molecular interactions and pharmacokinetic parameters of Guaiacol as a stimulant in renal tubular acidosis.…”
Section: Introductionmentioning
confidence: 99%